IMPLEMENTATION OF THE ACTIVITY REFOCUSING POLICY AND REALLOCATION OF THE REGIONAL GOVERNMENT BUDGET FOR THE SPECIAL CAPITAL CITY OF JAKARTA DURING THE COVID-19 PANDEMIC - Muhammad Sabana; Nur Ikawati; Kumba Digdowiseiso (SEAN Institute, 2023)
The DKI Jakarta Provincial Government during the Covid-19 pandemic tried to overcome economic problems by taking a policy of refocusing activities and reallocating the budget. The DKI Jakarta Provincial Government in this case through instructions from the Ministry of Home Affairs is also required to refocusing activities and reallocating the budget through changes in the REGIONAL BUDGET. In this study, we analyzed and provided solutions for the formulation of policies for refocusing activities and reallocating the budget of the DKI Jakarta Provincial Government during the Covid-19 pandemic. This research uses a narrative descriptive qualitative method with various litertaurs. The results of this study show that there are variations in changes in the APBD in refocusing activities and budget reallocation caused by several things, especially the absence of clear guidelines in refocusing activities and budget reallocation. In dealing with these problems, solutions that can be implemented by the DKI Jakarta Provincial Government Government is to create a kind of Standard Operating Procedure (SOP) that contains limits in the scope of the budget and activities that must be reduced, supplemented, or readjusted.